Simultaneous Estimation of Aceclofenac and Paracetamol by HPTLC in Pure and Pharmaceutical Dosage Form - HARIKRISHNAN, N.; GUNASEKARAN, V.; SATHISHBABU, A.; SRINIVASA RAO, G.; ROOSEWELT, C. (Asian Journal of Chemistry, 2010)
A simple, accurate, precise and reproducible high performance thin layer chromatographic method has been developed for the simultaneous estimation of paracetamol and aceclofenac in pharmaceutical dosage forms. It was performed on TLC plate precoated with silica gel 60F254 as stationary phase using mobile phase comprising of toluene:isopropyl alcohol:ammonia (20:20:3, v/v/v) and the detection was carried out by UV detection at 254 nm showing Rf value of 4.8 for aceclofenac and 11.8 for paracetamol. The percentage estimation of labeled claims of aceclofenac and paracetamol from marketed tablet was found to be 99.84 and 99.72, respectively. The method was validated in terms of accuracy, precision, specificity and ruggedness. Linearity was observed between 60-140 μg/mL for aceclofenac and 460-540 μg/mL for paracetamol. The recovery studies were carried out by adding known quantity of standard drugs in the pre-analysed test solution and percentage recovery calculated in each case. The percentage recovery studies for paracetamol and aceclofenac were found within the range of 98.60-99.32 %. The proposed method was found to be accurate, precise, simple and rapid could be used for routine analysis.